CONSERVATIVE SURVEY OF MACHINE LEARNING AND DATA ANALYTICS - Omotosho, Oluyinka I (IJRDO -Journal of Computer Science Engineering, 2023)
Computing power has been increasing exponentially, meaning that processing power can be harnessed to solve more complex tasks. Two fields that have emerged alongside this rapid growth are data analytics, machine learning. Data analytic and Machine learning algorithms are two terms used interchangeably in the world of big data and statistical analysis, the line that divide these two related terms is so tiny that most data analyst forget about the existence of such line dividing and providing blur differences between data analytic and machine learning algorithms. In this study, the underlying the difference between these two related terms and their common and different applications is studied in a concise manner. Their impact in decision making for firms, organizations and cooperate bodies, their approaches to problem solutions, as well as their limitations.